2020
DOI: 10.1089/wound.2019.0943
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps Are Markers of Wound Healing Impairment in Patients with Diabetic Foot Ulcers Treated in a Multidisciplinary Setting

Abstract: Neutrophil extracellular traps (NETs) are associated with impaired wound healing in diabetes. This study evaluates the association between NETspecific markers and wound healing among diabetic foot ulcer (DFU) patients treated in a multidisciplinary setting. Approach: Clinical data of diabetic patients with active foot ulcers who presented to our team between January 1, 2016 and June 30, 2017 were recorded. The diabetic ulcer severity score (DUSS) and wound, ischemia, and foot infection (WIfI) score were calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 37 publications
2
74
0
Order By: Relevance
“…While a full evaluation of DFU biomarkers is outside the scope of this review, briefly, some recent reports of wound exudate biomarkers for DFU wound healing include epithelial neutrophil-activating protein (ENA)-78 [ 254 ], c-x-c motif chemokine ligand 6 (CXCL6) [ 255 ], and MMP-9 [ 256 ]. A number of serum biomarkers have been identified, including albumin [ 257 ], PLR and NLR [ 122 , 258 ], angiopoietin-like 2 (ANGPTL2) [ 259 ], lipoprotein-associated phospholipase A2 and interleukin-18 (IL-18) [ 260 ], pentraxin 3 [ 261 ], T-cell differentiation markers [ 262 ], stem/progenitor cells [ 263 ], as well as neutrophil extracellular traps (NETs)-specific markers [ 264 ]. Recent genomic analyses of DFU have utilized circRNAs [ 265 , 266 , 267 ], lncRNAs [ 268 ], miRNAs [ 99 , 100 , 269 ], genetic polymorphisms [ 270 , 271 , 272 ], cytokine arrays [ 273 ], and network maps [ 274 ] for the identification of other potential biomarkers for DFU diagnosis and prognosis.…”
Section: Diagnostic Measuresmentioning
confidence: 99%
“…While a full evaluation of DFU biomarkers is outside the scope of this review, briefly, some recent reports of wound exudate biomarkers for DFU wound healing include epithelial neutrophil-activating protein (ENA)-78 [ 254 ], c-x-c motif chemokine ligand 6 (CXCL6) [ 255 ], and MMP-9 [ 256 ]. A number of serum biomarkers have been identified, including albumin [ 257 ], PLR and NLR [ 122 , 258 ], angiopoietin-like 2 (ANGPTL2) [ 259 ], lipoprotein-associated phospholipase A2 and interleukin-18 (IL-18) [ 260 ], pentraxin 3 [ 261 ], T-cell differentiation markers [ 262 ], stem/progenitor cells [ 263 ], as well as neutrophil extracellular traps (NETs)-specific markers [ 264 ]. Recent genomic analyses of DFU have utilized circRNAs [ 265 , 266 , 267 ], lncRNAs [ 268 ], miRNAs [ 99 , 100 , 269 ], genetic polymorphisms [ 270 , 271 , 272 ], cytokine arrays [ 273 ], and network maps [ 274 ] for the identification of other potential biomarkers for DFU diagnosis and prognosis.…”
Section: Diagnostic Measuresmentioning
confidence: 99%
“…This uptake of neutrophil-derived apoptotic bodies’ by infiltrating monocytes/macrophages helps resolve the inflammatory phase in a self-perpetuating manner by limiting inflammatory cell infiltration and shifting the production of eicosanoids from pro-inflammatory to anti-inflammatory mediators [ 22 , 23 , 24 ]. Unfortunately, however, in diabetic wounds the inflammatory phase is significantly prolonged by the disruption of mechanisms which both control the influx of neutrophils as well as regulate their inflammatory processes [ 12 , 21 , 25 ]. Interestingly, it seems that the cause of many observed dysregulations of the inflammatory phase is not directly associated with localized high glucose levels but rather the epigenetic polarization of innate immune cell pro-inflammatory function prior to wound infiltration, as in progenitor cell modification due to T2DM-related systemic complications such as hyperglycemia [ 26 ].…”
Section: Wound Inflammation Orchestrates Healing and Regenerationmentioning
confidence: 99%
“…The level of neutrophil NETs-specific markers, such as citrullinated histone H3 (citH3), is higher in DFU compared to DFU-deficient and healthy patients. It was reported that NETs, released by neutrophils, contributed to delaying wound healing [ 117 ]. Thus, the inhibition of NETs may facilitate ameliorated wound healing in diabetic mice.…”
Section: Chronic Wound Healingmentioning
confidence: 99%